Exploring Oral Corrective Feedback on Students English Speaking Performance Within Indonesian Context: A Systematic Literature Review - Deni Yatri; Risya Astrifiya Cahyani; Galita Febrian Pratidina; Anam Fadillah; Utami Widiati (Transpublika Publisher, 2025)
This systematic literature review synthesizes research on oral corrective feedback (OCF) and its effects on students' speaking performance within the Indonesian context. Following the PRISMA guidelines, 19 studies published between 2014-2024 were analyzed. The findings reveal diverse OCF practices employed by teachers, with explicit correction and recasts being the most commonly used types. However, a key challenge lies in the mismatch between the OCF strategies preferred by students, such as explicit correction and metalinguistic clues, and those predominantly used by teachers. OCF was found to evoke both positive emotions like motivation and perceived importance, as well as negative emotions including embarrassment, lowered confidence, and nervousness about making mistakes. The studies underscore the need for teachers to consider factors such as error types, timing of correction, students' proficiency levels, and potential emotional impacts when providing OCF. Tailoring OCF practices to individual student needs and preferences emerges as crucial for optimizing effectiveness and fostering a supportive learning environment.